2019
DOI: 10.3390/ijms20194722
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BpCUC2 Influences Leaf Shape and Internode Development in Betula pendula

Abstract: The CUP-SHAPED COTYLEDON 2 (CUC2) gene, which is negatively regulated by microRNA164 (miR164), has been specifically linked to the regulation of leaf margin serration and the maintenance of phyllotaxy in model plants. However, few studies have investigated these effects in woody plants. In this study, we integrated genomic, transcriptomic, and physiology approaches to explore the function of BpCUC2 gene in Betula pendula growth and development. Our results showed that Betula pendula plants overexpressing BpCUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Eventually, the explants were placed onto co-cultivation medium (WPM with 0.8 mg/L 6-BA, 0.02 mg/L NAA) under dark for 2 days and then planted on selective medium (WPM with 2.0 mg/L 6-BA, 0.02 mg/L NAA, 5.5mg/L hygromycin or glufosinate ammonium and 200 mg/L cefotaxime). After 30 days, resistant adventitious buds were induced (WPM with 2.0mg/L 6-BA, 0.02 mg/L NAA, 0.5mg/L GA,5.5mg/L hygromycin or glufosinate ammonium and 200 mg/L cefotaxime) and rooted (WPM + 0.4mg/L IBA) ( Liu et al, 2019 ). After raised to 5 cm high in growth chamber, transgenic plants were transferred to the greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, the explants were placed onto co-cultivation medium (WPM with 0.8 mg/L 6-BA, 0.02 mg/L NAA) under dark for 2 days and then planted on selective medium (WPM with 2.0 mg/L 6-BA, 0.02 mg/L NAA, 5.5mg/L hygromycin or glufosinate ammonium and 200 mg/L cefotaxime). After 30 days, resistant adventitious buds were induced (WPM with 2.0mg/L 6-BA, 0.02 mg/L NAA, 0.5mg/L GA,5.5mg/L hygromycin or glufosinate ammonium and 200 mg/L cefotaxime) and rooted (WPM + 0.4mg/L IBA) ( Liu et al, 2019 ). After raised to 5 cm high in growth chamber, transgenic plants were transferred to the greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that CUC2 plays important roles in adventitious shoot formation ( Daimon, Takabe & Tasaka, 2003 ) and floral organ development ( Aida et al, 1997 ; Baker et al, 2005 ; Kamiuchi et al, 2014 ; Gonzalez-Carranza et al, 2017 ). Moreover, CUC2 plays a role in internode development, with BpCUC2 overexpression leading to internode shortening in Betula pendula ( Liu et al, 2019 ). Taken together, these observations suggest that CUC2 participates in both growth and development in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Plants were cut and grown on 0.2 mg L −1 NAA 0.5 Murashige and Skoog (0.5 MS) medium with 1% sucrose and 0.75% agar (pH 6) (16-h light and 8-h dark photoperiod) when the adventitious buds grew up. At 1-month-old, seedlings in 1 2 MS medium were transplanted into a 45-plug tray (3 cm in diameter by 3 cm in height). The seedling growth substratum was black soil (v/v):perlite:vermiculite (4:2:2) and maintained in a growth room at 24 ± 1 • C with a 16-h light and 8-h dark photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…White birch (Betula platyphylla S.) is a revolutionary forest plant in northeastern China [1], which is one of the most valuable, important, and widely distributed tree species in east Asia, mostly in China, Korea, and Japan [2]. Betula platyphylla has a rapid growth rate, excellent material properties, high artificial planting survival rate, and a wide range of applications in the manufacture, pharmacy, and landscaping of furniture [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation